Nghiên cứu tính khả tuyển vermiculit vùng Vinh Tiến-Khả Cửu, Thanh Sơn, Phú Thọ - Lưu, Văn Thắng (2011)
Tác giả: Lưu Văn Thắng, KS; Nguyễn Đình Tiết, KS; Nguyễn Thanh Tùng, ThS; Trần Thị Thanh Phúc, KS; Nguyễn Kim Thu, KS -- Từ khóa: Tuyển quặng; Vermiculit; Thanh Sơn; Phú Thọ